An Influence of Gender and School Location on Study Habit Behaviour among Secondary School Students in Lagos State - Adekola Kamil Lasisi; Abdulmutalib Opeyemi Adio; Abdulmutalib Opeyemi Adio (Universitas Pendidikan Ganesha, 2024)
The study explored the intersection of gender and school location on study habits among secondary school students in Lagos State, with a specific focus on the Alimosho Local Government Area. By evaluating 800 senior secondary students, with 80 selected through purposive sampling across three schools, the research aimed to provide insights into how these factors influence study habits. Utilising the Students Study Habits Inventory validated by Akinnade (2017), the study uncovered significant differences in study habits between genders, with males exhibiting more favorable study habits compared to females. This finding suggests that there may be underlying socio-cultural or educational factors shaping study behaviors differently for males and females in the context of Lagos State secondary schools. In contrast, while the study noted a potential association between school location and study habits, it did not reach statistical significance (p > 0.05). Based on these findings, several recommendations were proposed to enhance study habits among secondary school students. One suggestion involved implementing extra educational initiatives, such as the Students Interactive Programme, specifically tailored to address the needs of female students during post-school hours. This recognizes the importance of providing targeted support and resources to bridge the gender gap in study habits. Overall, the study highlights the importance of considering both gender and school location in understanding and addressing study habits among secondary school students in Lagos State. By implementing targeted interventions and support mechanisms, educational stakeholders can work towards fostering a conducive learning environment that promotes equitable access to academic success for all students, regardless of gender or geographical location.